2017
DOI: 10.1186/s12882-017-0776-2
|View full text |Cite
|
Sign up to set email alerts
|

MDRD vs. CKD-EPI in comparison to 51Chromium EDTA: a cross sectional study of Malaysian CKD cohort

Abstract: BackgroundAccurate measurement of renal function is important: however, radiolabelled gold standard measurement of GFR is highly expensive and can only be used on a very limited scale. We aim to compare the performance of Modification of Diet in Renal Disease (MDRD) and Chronic Kidney Disease-Epidemiology Collaboration (CKD-EPI) equations in the multi-ethnic population attending University Malaya Medical Centre (UMMC).MethodsThis is a cross-sectional study recruiting patients, who attend UMMC Nephrology clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…First, our study was a single-center observational cohort with only Chinese patients, the results may not be applicable to other populations. Second, CKD-EPI equation using creatinine has been proved to be more accurate than MDRD equation and has been recommended by current guidelines [15,24]. However, in our study, the mean age of the patient was 71.2 years.…”
Section: Limitationsmentioning
confidence: 53%
“…First, our study was a single-center observational cohort with only Chinese patients, the results may not be applicable to other populations. Second, CKD-EPI equation using creatinine has been proved to be more accurate than MDRD equation and has been recommended by current guidelines [15,24]. However, in our study, the mean age of the patient was 71.2 years.…”
Section: Limitationsmentioning
confidence: 53%
“…The number of other publications also showed that probably the best creatinine-based equation in general population is the CKD-EPI. 7,[14][15][16]19,20 However, the differences between CKD-EPI and MDRD were often very slight and the advantage of CKD�EPI was not significant in patients with CKD staged 3 or more. 7,16,20 Furthermore, for population of elderly patients, like in our examined group, the advantage of CKD-EPI has not been proved and most of examined patients were under age of 65 years or at least part of tested population suffered from diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…7,[14][15][16]19,20 However, the differences between CKD-EPI and MDRD were often very slight and the advantage of CKD�EPI was not significant in patients with CKD staged 3 or more. 7,16,20 Furthermore, for population of elderly patients, like in our examined group, the advantage of CKD-EPI has not been proved and most of examined patients were under age of 65 years or at least part of tested population suffered from diabetes. 7,[12][13][14][15][16] In fact, there was only one examination that comparing eGFR equations, performed on the group of 398 elderly patients truly similar to ours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations